2022
DOI: 10.3389/fpls.2022.969852
|View full text |Cite
|
Sign up to set email alerts
|

Different contributions of plant diversity and soil properties to the community stability in the arid desert ecosystem

Abstract: As a one of the focuses of ecological research, understanding the regulation of plant diversity on community stability is helpful to reveal the adaption of plant to environmental changes. However, the relationship between plant diversity and community stability is still controversial due to the scale effect of its influencing factors. In this study, we compared the changes in community stability and different plant diversity (i.e., species, functional, and phylogenetic diversities) between three communities (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…The addition of 3% SBC, 5% SBC and 5% FBC decreased the relative abundance of dominant species compared with other biochar. According to the “Complementary Effect”, an increase in biodiversity promotes complementary resource utilization through niche complementation ( Wang et al., 2019 ; Jiang et al., 2022 ; Token et al., 2022 ). Moreover, we also found the positive correlation between the FDis index and community stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of 3% SBC, 5% SBC and 5% FBC decreased the relative abundance of dominant species compared with other biochar. According to the “Complementary Effect”, an increase in biodiversity promotes complementary resource utilization through niche complementation ( Wang et al., 2019 ; Jiang et al., 2022 ; Token et al., 2022 ). Moreover, we also found the positive correlation between the FDis index and community stability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also found the positive correlation between the FDis index and community stability. Functional dispersion serves as an indicator of niche complementarity, with higher values reflecting stronger competition and niche complementarity among species ( Jiang et al., 2022 ). The increase in functional dispersion contributes to maintaining community stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the "niche complementarity effect" between species has an important impact on community stability. When the traits between species are different, this can stimulate the community to secure more resources, reduce intraspecific competition, and improve community stability [13]. A meta-analysis showed that on a global scale, plant species diversity increased the soil microbial biomass, fungal-bacterial biomass ratio, and respiration in terrestrial ecosystems [8].…”
Section: Introductionmentioning
confidence: 99%
“…Affected by harsh environments (i.e., low soil water and nutrient availability, high soil salinity and frequent wind disturbance), ecosystem in the ELWNR is highly sensitive and fragile to environmental changes (Wang et al, 2021). In contrast, the ELWNR is a resource treasury of biodiversity in arid desert areas (Jiang et al, 2022), which has well-protected and typical riparian forests in northwest China. It offers an eligible place for investigating the spatial relationship between species diversity and soil properties.…”
Section: Introductionmentioning
confidence: 99%